4
$\begingroup$

Find all functions such that $f(x)f(y) = f(xy + 1) + f(x - y) – 2$ for all $x, y $ are real numbers.

I put y=0 into the equation and get $(f(0)-1)f(x)=f(1)-2$. If $f(0)≠1$, then $f(x) = (f(1)-2)/(f(0)-1)$ and so the function would be constant. But, since $c^2=2c-2$ has no real solutions, the function cannot be constant. Hence, $f(0)=1$, which implies that $f(1)=2$. Also note that f must be an even function as $f(x-y)=f(y-x)$.
Set $f(x)=1+x^2+g(x)$ for some even function of $g$, with $g(0)=g(1)=0$. Then put $f(x)$ into the functional equation and substitute $y=1$, get $g(x+1)-g(x)=g(x)-g(x-1)$. Define $P(x) = {…, g(x-2), g(x-1), g(x), g(x+1), g(x+2),…}$ , so $P(x)$ is an A.P. Then substitute $y = -x , y=x$ and using the fact that g is even, to get $g(x^2+1) – g(x^2-1) = g(2x)$. I’m trying to prove $g(x)=0$ for all $x$. How can I proceed?

$\endgroup$
3
$\begingroup$

Let $S=\{\,x\in \Bbb R\mid f(x)=x^2+1\,\}$. You already know: $f(0)=1$, $f(1)=2$, $f$ is even, i.e., $\{0,1\}\subset S$ and $S=-S$. We want to show $S=\Bbb R$, and this is equivalent to your endeavour to show $g\equiv 0$, but I find it easier to think of it this way.

One readily sees from the fact that $x\mapsto x^2+1$ solves the functional equation:

$$\tag0\text{If three out of }x,y,xy+1,x-y\text{ are }\in S\text{, then so is the fourth.}$$

With $y=1\in S$, this becomes $$ \tag1\text {If two of }x-1,x,x+1\text{ are }\in S\text{, then so is the third.}$$ From this and $0,1\in S$, induction gives us $$\Bbb Z\subset S.$$ Likewise, with $x=y$ and using $0\in S$, $(0)$ becomes $$ \tag2\text{If }x\in S\text{, then }x^2+1\in S.$$ More precisely, $y=x$ gives us $$ \tag 3f(x)^2+1=f(x^2+1),$$ and so $$\tag4 f(x)\ge 1\quad\text{for }|x|\ge 1.$$ Consider $x$ with $0<|x|<1$. With $y=2\operatorname{sgn}(x)+x$, we get that $|y|>1$, $|xy+1|>1$, $y-x=\pm2$ so that by $(4)$, $f(x)f(y)=f(xy+1)+3\ge 4$, and hence $f(x)>0$. Thus together with $(4)$ and $f(0)=1$, $$ f(x)>0\qquad\text{for all }x\in\Bbb R.$$ This and $(3)$ allows us to improve $(2)$ to $$ \tag5x\in S\iff x^2+1\in S.$$ For $0\le u_0<v_0$, let $u_n=u_{n-1}^2+1$, $v_n=v_{n-1}^2+1$. Then $u_n<v_n$, $(u_{n-1},v_{n-1})$ is mapped bijectively to $(u_n,v_n)$ by $x\mapsto x^2+1$, and $$v_n-u_n=(u_{n-1}+v_{n-1})(v_{n-1}-u_{n-1})>2u_{n-1}(v_{n-1}-u_{n-1})\ge 2(v_{n-1}-u_{n-1})$$ for $n\ge 2$, hence some interval $(u_n,v_n)$ will have length $>1$ and therefore intersect $\Bbb Z$ and also $S$. We conclude from $(5)$ that also $(u_0,v_0)$ intersects $S$, hence $$ \overline S=\Bbb R.$$ In other words,

$f(x)=x^2+1$ is the only continuous solution of the functional equation.

$\endgroup$
2
$\begingroup$

A way to show that $g(x)=0$ is the only continuous solution is to show that $g(q)=0$ for all rational $q$. To do this, substitute $x=\frac mn$ and $y=n$ ($m,n\in\mathbb{Z}$, $n\ne0$) into the equation and we get $$\tag1(1+n^2)\ g\left(\frac mn\right)=g\left(\frac mn-n\right)$$

Now, let $d(x)=g(x+1)-g(x)$. We have $d(-x)=-d(x)$. But $(1)$ implies that $$g\left(\frac mn\right)=-\frac 1n\ d\left(\frac mn\right)$$ $m\rightarrow-m$ then shows that $g\left(\frac mn\right)=0$, as desired.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.